Highly ordered mesoporous silica film nanocomposites containing gold nanoparticles for the catalytic reduction of 4-nitrophenol - Jalani M.A.; Yuliati L.; Lee S.L.; Lintang H.O. (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2024)
Indexed by Scopus